Comparative assessment of the survival, stability and occlusal settling between two types of thermoplastic retainers: a prospective clinical trial - Cunning Bethany; Sahhar Alison; Lawrence Sarah; Manton David; Schneider Paul (Sciendo, 2022)
A controlled clinical trial was undertaken to compare the effectiveness of Vivera® and Duran® retainers with regard to the survival, stability and occlusal settling over the first 6 months of retention following the completion of clear aligner treatment.